Metabolism - Suhr F (Dynamic Media Sales Verlag, 2019)
Physical exercise evokes mechanical loading conditions and thereby controls a diversity of physiological and biological reactions ranging from improved endurance capacity to increased muscle strength.This holds true for the endothelial cell system, which is controlled by exercise-dependent shear forces and for the skeletal muscle system subjected to mechanical loading. Shear forces/mechanical loading result in the activation of proteolytic enzymes, called proteases, which are capable of remodeling the central mechanosensitive cell scaffold, the extracellular matrix (ECM). Remodeling of ECM components evokes the release of cleavage fragments. These cleavage fragments in turn exert defined biological functions, such as angiogenesis modulation, nitric oxide generation or muscle regulation. This mini-review (i) describes the main players involved in this processing cascade and discusses the influence of physical exercise on mechanisms of ECM remodeling in the endothelial cell and muscle systems and (ii) discusses influences of societal challenges, such as aging or chronic diseases on ECM remodeling. KEY WORDS: ECM, Exercise, Endothelial Cells, Skeletal Muscle